The Effort to Healthy Pregnancy Through Education on Physical Activity, Nutrition and Body Mechanics - Khanifah, Milatun; Kristiyanti, Rini; Fitriyana, F; Suparni, S; Yunianti, Erma (Universitas Muhammadiyah Surakarta, 2023)
Pregnancy as a physiological process is often an obstacle to maintaining optimal health due to the discomfort that occurs during this period. Various obstacles due to discomfort can prevent pregnant women from being physically active, implementing a healthy diet. In addition, in the 3rd trimester of pregnancy, most pregnant women experience the discomfort of back pain, and many are not aware of the management that can be done. This condition causes pregnant women to be unfit during the pregnancy process. This community service program aims to increase the knowledge of pregnant women related to physical activity, nutrition and body mechanics so that the pregnancy is a quality process. This community service was conducted in Noyontaansari sub-district, the working area of Pekalongan City Noyontaan Health Center, which 29 pregnant women attended. The activity was carried out through education in pregnant women's class activities. There was an increase in the knowledge level of pregnant women before and after the education. The knowledge tested included knowledge about physical activity (exercise), nutrition, and body mechanics for pregnant women. The pre-test results showed that most (62%) had a moderate level of knowledge, 7% had less knowledge and only 31% had good knowledge. After the training, the post-test results showed that all pregnant women had a good level of knowledge. This is an indication of the success of the PkM activities in improving knowledge.